Functionally graded graphene reinforced porous nanocomposite curved beams: Bending and elastic stability using a higher-order model with thickness stretch effect. (1st June 2019) - Polit, O.; Anant, C.; Anirudh, B.; Ganapathi, M.
Abstract: Here, the investigation of thick functionally graded graphene platelets reinforced porous nanocomposite curved beams is carried out considering the static bending and elastic stability analyses based on a higher-order shear deformation theory accounting for through-thickness stretching effect. The formulation is general through which different theories can be realized for various structural applications of beam. The governing equations are developed using the Hamilton's principle and are solved by introducing the Navier's solutions. The formulation is firstly assessed considering problems for that results are available in the literature. The performance of various theories is compared here for the selected problems. The structural characteristics of curved beam, constituting of porous metal foam and graphene platelets as nanofillers for reinforcement, are evaluated considering different dispersion patterns for the graphene and porosity, shallowness of the curved beam, thickness ratio, and platelet geometry. The deflection and stress variations in the thickness direction of the beam are also examined. Highlights: Bending and stability of FG graphene reinforced porous nanocomposite curved beams by a higher-order theory with thickness stretching effect. Introduction of different distributions for porosity and graphene platelets in the beam. Analytical solutions for thick and thin, shallow and deep curved beams by Navier's approach. Comparative study made considering different theories deduced from present formulation. Detailed investigation made considering many material and geometric parameters.